Post-traumatic endophthalmitis in children - Venkatesh, Ramesh; Dave, Abhishek Prachi; Gurav, Prachi; Agrawal, Manisha (Nepalese Journal of Ophthalmology, 2019)
Purpose: To study the clinico-microbiological profile and evaluate the functional and anatomical outcomes of pediatric post-traumatic endophthalmitis (PPTE). Methods: This was a retrospective interventional case series. All medical case records of patients diagnosed with PPTE over a 5-year period from January 2011 to December2015 were reviewed. Data recorded was: age, sex, type of trauma, mode of injury, interval between trauma and presentation, treatment, follow-up duration and final functional and anatomical outcomes. Results: Forty-one eyes of 41 patients diagnosed with PPTE met the inclusion criteria. There were 26 boys and 15 girls. The mean age at the time of presentation was 7.34 years (1month -16years). The median interval between trauma and presentation was 3 days (mean = 13.71 days; 1-240 days). The average follow-up period was 292.24 days (median 150 days; 30 1440 days). Injury with wooden stick (20,50%) was the most common mode of injury. Culture positivity was noted in 25(61%) cases. Staphylococcusaureus was the most common organisms identified on culture. Univariate analysis of in dependent variables was done using the Chi-square test showed patients with positive culture for gram-positive organisms had better anatomical (p=0.038) and functional outcomes (p=0.043). 35(85%) patients underwent vitrectomy along with intraocular antibiotics. Optimal anatomical and functional outcomes were noted in 23(56.1%) and12(29.3%) respectively. Conclusion: PPTE carries a significantly poor prognosis in terms of ocular integrity and visual function. PPTE is common in boys and often caused by vegetative matter. Staphylococcus aureus is the most common organism seen in PPTE. Early presentation following trauma and identification of gram-positive organisms have a better prognosis.